Body weight training versus series 7 diabetes dance: their influence on glucose levels in patients with type 2 diabetes mellitus - Muhammad, Dikri; Sumarjo, Sumarjo; Kushartanti, BM Wara; Nourzad, Fatemeh (Jurnal Keolahragaan, 2024)
Managing blood glucose levels is critical for preventing complications associated with type 2 diabetes mellitus (T2DM). Physical activity has been shown to be an effective strategy for glucose control, with various forms of exercise yielding different results. This research aims to explore the effects of body weight training and series 7 diabetes dance on reducing blood glucose levels in patients with T2DM, and to compare the efficacy of these two interventions in achieving glucose control. The type of research was a quasi-experiment with a two groups pre-test post-test design. The series 7 diabetes dance group performed the exercise 4 times a week (duration: 170 minutes 8 seconds/week), while the body weight training group performed exercise 3 times a week (8 movements, number of repetitions close to failure, circuit system, 3 sets per training session). Both groups were doing an exercise program for three months. The research sample was for about 16 patients of type 2 diabetes mellitus (8 people per group, devided randomly), taken by using non probability sampling technique, purposive sampling type (effect size 1.6, significant level (Î±) 0.05 and Power 0.8). The data analysis used the paired sample t test and the independent t test with a significance level of Î± = 0.05.The results showed that 1) there is no significant effect of series 7 diabetes dance towards the decreasing the level of blood sugar of the patients with type 2 diabetes mellitus), 2) there is a significant effect of body weight training towards the decreasing level of blood glucose of the patients with type 2 diabetes mellitus, 3) dody weight training is more effective in decreasing the level of blood glucose of patients with type 2 diabetes mellitus compared to series 7 diabetes dance. Future research must be carried out as a true experiment with a larger number of samples and with the HbA1c research instrument.